Pengaruh PVA terhadap kestabilan nanopartikel tembaga dari CuSO4 menggunakan bioreduktor kulit buah naga merah (Hylocereus costaricensis) - Suriati Eka Putri; Achmad Fudhail; Rosmala Rauf (Seminar Nasional LP2M UNM, 2019)
Has been done a research about synthesis of copper nanoparticles using CuSO4 and bioreductor of extract Hylocereus costaricensis skin. The aim of this study was to determine the influence of PVA towards the stability of copper nanoparticles. Copper nanoparticles are made through a reduction method. The bioreductor solution and precursor are mixed with volume variations 1: 1, 1: 2, 1: 3, and 1: 4. Copper nanoparticles that are. The highest chemical content of copper nanoparticles is Cu of 82.29%. The presence of fixed PVA affects the stability of naoparticles where without the addition of PVA copper nanoparticles form an aggregate and become unstable.